HUBUNGAN PENGUASAAN KOSAKATA BAHASA INDONESIA DENGAN KETERAMPILAN MENULIS TEKS NEGOSIASI KELAS X IPA 2 SMA NEGERI 5 BUKITTINGGI TAHUN PELAJARAN 2016/2017 - Mustyka, Olyvia (Aksara Public, 2018)
This research type is quantitative research with correlational methods. The population in this study directly into the sample amounted to 37 people. The technique used sampling is total sampling 100 people. Variable in this research there are two, namely dependent variable and independent variable. This research data in the form of objective test result in the form of multiple choice for vocabulary test and student eriting skill text writing skill obtained through performance tes. The collected data is analyzed according to the indicator by using normality test and linearity test. Hypotheses tested using product miment correlation formula between the mastery of Indonesian language with the skills of writing negotiation text and test the significance of correlation used. The result of data analysis shows that the average ability of vocabulary mastery is higher than the negotiating text writing skill. The use of product moment correlation formula yields a magnitude of 0,43 whereas the use of t test rumus produces r arithmetic 2,817. The hypothesis reads â€œthere is a significant relationship between vocabulary mastery with the skill of writing the negotiation text of the students of class X IPA 2 SMA Negeri 1 Bukittinggiâ€, â€œacceptedâ€. Thus is said because t count is greater than t table (2,817>2,030). Thus it can be concluded that there is a significant relationship between the mastery of Indonesian vocabulary with the skills to write the text of the negotiation of class X student IPA 2 SMA Negeri 1 Bukittinggi